2022
DOI: 10.1111/1751-7915.14104
|View full text |Cite
|
Sign up to set email alerts
|

Continuous feeding strategy for polyhydroxyalkanoate production from solid waste animal fat at laboratory‐ and pilot‐scale

Abstract: Bioconversion of waste animal fat (WAF) to polyhydroxyalkanoates (PHAs) is an approach to lower the production costs of these plastic alternatives. However, the solid nature of WAF requires a tailor‐made process development. In this study, a double‐jacket feeding system was built to thermally liquefy the WAF to employ a continuous feeding strategy. During laboratory‐scale cultivations with Ralstonia eutropha Re2058/pCB113, 70% more PHA (45 g PHA L −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 50 publications
(83 reference statements)
0
9
0
1
Order By: Relevance
“…To perform fed-batch cultivations, a new system had to be developed to transfer the solid FPE into the bioreactor. The inability to liquefy the FPE made it impossible to pump the feedstock to the bioreactor as described in a previous study (Gutschmann, Maldonado Simões, et al, 2022). The principal concept to transfer the substrate was to use high pressure for its delivery into the bioreactor.…”
Section: Development Of a Pneumatic Feeding Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…To perform fed-batch cultivations, a new system had to be developed to transfer the solid FPE into the bioreactor. The inability to liquefy the FPE made it impossible to pump the feedstock to the bioreactor as described in a previous study (Gutschmann, Maldonado Simões, et al, 2022). The principal concept to transfer the substrate was to use high pressure for its delivery into the bioreactor.…”
Section: Development Of a Pneumatic Feeding Systemmentioning
confidence: 99%
“…One approach to tackle this problem is the preliminary conversion of waste animal fats to biodiesel and the subsequent usage of the glycerol and saturated fatty acid methyl ester phases for PHA production (Koller & Braunegg, 2015 ; Muhr et al, 2013 ). Another strategy is the thermal liquefaction of waste animal fats and direct feeding into an existing emulsion formed with plant oil in Ralstonia eutropha cultivations (Gutschmann, Maldonado Simões, et al, 2022 ; Riedel et al, 2015 ). The latter approach makes use of a natural emulsification process, which is catalysed by extracellular lipases and eventually stabilized by extracellular polysaccharides (Gutschmann et al, 2021 ; Lu et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…PHA accumulation increased 3.18-fold compared to the wild-type strain. In addition to waste vegetable fats, solid waste animal fat was also used to produce PHA (Gutschmann et al 2023 ). The Cupriavidus necator (formerly Ralstonia eutropha ) Re2058/pCB113 strain used produced 45 g PHA/L (a double-jacket feeding system was created to thermally liquefy the waste animal fat to employ a continuous feeding strategy).…”
Section: Phas Production From Side-streamsmentioning
confidence: 99%
“…Gutschmann, Maldonado Simões, et al ( 2022 ) reported the bioconversion of waste animal fat (WAF) to polyhydroxyalkanoates (PHAs) in laboratory scale reactors utilizing Ralstonia eutropha Re2058/pCB113, obtaining 45 gPHA/L a space–time yield of 0.63 gPHA/L/h. Surprisingly, minimal PHA accumulation (31.5 gPHA L −1 ) was reported in a 150‐L pilot scale reactor equipped with three 6‐blade Rushton impellers, likely due to the following factors: (i) insufficient or variable WAF, (ii) scale‐up effects and (iii) dense foam formation.…”
Section: Polyhydroxyalkanoate (Pha) Production From Wastesmentioning
confidence: 99%